The potential and strategy of zakat collection from workers in the Federal Territory - Duasa, Jarita; Afroz, Rafia (2019)
The present study attempts to identify the level of understanding and the practice of foreign workers as regards to zakat and fitrah in the Federal Territory; to identify the amount of potential collection and number of foreign workers in the Federal Territory who are zakat payers; to recommend the best zakat collection management and marketing strategy to attract foreign workers in the Federal Territory to pay zakat of income and fitrah at the Zakat Collection Center (PPZ); and to analyze the factors that contribute to the probability of Muslim foreign workers choose to pay zakat and fitrah in Malaysia. The primary data are collected through survey on foreign workers and several methods of analysis are used in the study including descriptive analysis, cross tabulation analysis with the use of Chi-square tests, correlation analysis, steps in estimation of potential zakat collection and regression analysis. The findings show that despite good general knowledge and awareness of foreign workers on zakat, they have very limited knowledge and awareness on zakat system in Malaysia. It is also estimated that potential collection of zakat income from Muslim foreign workers in 2019 is between RM100,125,448 and RM115,482,862. The regression analysis shows that probability of paying zakat income among foreign workers is higher among male workers, highly educated workers and those who have knowledge about zakat income. The probability that foreign workers opt to pay zakat fitr is higher among those with better knowledge about this type of zakat. Besides, the likelihood that foreign workers will pay zakat in Malaysia in the future is lower for those who have professional/PhD education and the likelihood is higher if the reason of not paying zakat in Malaysia is ‘do not have knowledge on how to pay zakat in Malaysia’.